Investigating Students’ Strategy in Conducting Independent Learning at SMP 12 Binjai - Winny Meilita Lubis (Universitas Negeri Medan, 2025)
This study aims to investigate the strategies used by seventh-grade students at SMP Negeri 12 Binjai in conducting independent learning in English. This study uses a qualitative research design, data collected through a questionnaire consisting of open-ended questions. The instrument, a carefully structured questionnaire, was administered to the students, whose responses served as the primary data source. The data were analyzed using a descriptive qualitative approach through data reduction, categorization, and conclusion drawing, following Miles and Huberman’s (1994) framework. The findings reveal that students applied various strategies aligned with Zimmerman’s (2000) three-phase model of self-regulated learning: forethought, performance, and self-reflection. In the forethought phase, students engaged in goal-setting and planning; during the performance phase, they managed time and minimized distractions; and in the self-reflection phase, they evaluated their learning progress. The study concludes that while students demonstrate foundational self-regulated learning behaviors, there remains a need for more structured guidance to deepen their metacognitive skills and enhance their overall learning autonomy.